Mobile-Phone Based Patient Compliance System for Chronic Illness care in Nigeria - Akinbode, O. P. (2012)
To improve chronic illness care, patients must be empowered and engaged in health self-management. However, only half of all patients with chronic illness comply with treatment programme. The self-regulation model needs practical tools to help patients adopt this selfcentered approach for long-term care. This research work considered a Mobile-phone based Patient Compliance System (MPCS) that can reduce the time-consuming and error-prone processes of existing self-regulation practice to facilitate self-reporting, non-compliance detection, and compliance reminder among patients in Nigeria. The uniqueness of this work is to apply social behavior theories to engineer the MPCS to positively influence patients' compliance behaviors, including mobile-delivered contextual reminders based on association theory; mobiletriggered questionnaires based on self-perception theory; mobile enabled social interactions based on socialconstruction theory, also explained how mobile phone can help patient to comply to their medication treatment; the existence of mobile phones and its uses in health sectors in Nigeria.